POTENSI PEMBANGUNAN MASYARAKAT PESISIR SELATAN DIY MASALAH DAN TANTANGANNYA - Imamudin Yuliadi (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
Indonesia is one country that have longest coast in the world because Indonesia consist of many archipelago. This fact give implication that economic is potential factors for people life at the coastal areas to economic growth for improving walfareand equity on economic development both national and regional scope. The role of fisherman is very strategic to improve economic growth, even that their condition is below average economic welfare. Source of data from government office like statistical center agency, Bank Indonesia and many else. Research methodology that applied is desriptive investigative to obtain the fact about the economic problem of people at thecoastal region for improving people economic welfare. Analitical methode at this research is location quation (LQ), shift-share, and typology of klassen. The output of this research is making the planning model of promotion system and integrated investment to realize the equility of economic development at southern coastal part of DIY.